Influence of demographic, food attributes, physical environment and service attributes on perceived value and overall satisfaction at casual dining restaurants in Klang Valley, Malaysia - Ahmad, Faridah (2015)
The increasing population has caused an increase in food demand and a change in eating pattern. Besides, the economic growth has influenced the urban population to spend more on eating outside home. Compared to other types of restaurants, the casualtype restaurants are now gaining attention and popularity. Hence, this study only focused on casual-type restaurants. Due to the mushrooming of casual dining restaurants, restaurant operators should create competitive advantage by offering greater benefits and providing a unique factor to be different from other competitors. Besides, failure in providing good services can cause loss in terms of sales, profits, and the number of customers dining at the restaurant. In fact, failure occurs when the service rendered fails to meet customers’ expectations. Therefore, the present study aimed to identify the restaurant attributes that influence customer perceived value at casual dining restaurant in Klang Valley. The second objective was to measure the relationship between restaurant attributes and perceived value at casual dining restaurant. The third objective was to measure the relationship between customers perceived value and overall satisfaction at casual dining restaurant. Finally, the perceived important attributes at casual dining restaurant will be determined through the present study. A total of 800 questionnaires were distributed. However, 682 usable responses were accepted for further analyses. Descriptive and inferential analyses were run by using IBM SPSS Statistics version 21. On top of that, this study discovered four restaurant attributes that influence customer perceived value. Service attributes, food attributes, physical environment, as well as innovative and convenience were found to have significant relationships with perceived value. Perceived value was also found to have a significant relationship with overall satisfaction. Overall, all relationships tested resulted in moderate positive correlations between variables. Moreover, the present study revealed fifteen items perceived as very important by customers. The findings obtained from this study is hoped to help practitioners in identifying significant attributes at casual dining restaurants to attract customers and increase customer’s perceived value. The perceived value could determine customers’ overall satisfaction. Additionally, this study has contributed to the enrichment of theoretical in identifying the important factors and restaurant experience. Moreover, this study has offered useful information that should benefit restaurant operators to improve their current strategies applied at casual dining restaurants in Klang Valley, Malaysia.